Ionic Conductive Membranes for Fuel Cells - Narducci, Riccardo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book, titled "Ionic Conductive Membranes for Fuel Cells", from the journal Membranes, discusses the state of the art and future developments in the field of polymer electrolyte membranes for fuel cells, an efficient and clean system for converting fuel into energy.